1996
DOI: 10.1093/mutage/11.5.435
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of centromeric DNA and prevention of homologous chromosome separation in male mouse meiosis in vivo by the topoisomerase II inhibitor etoposide

Abstract: The mechanism of action of the topoisomerase II inhibitor etoposide (VP-16) was investigated in male mouse meiosis using the spermatid micronucleus (MN) test and two molecular cytogenetic approaches: (i) fluorescence in situ hybridization (FISH) with a mouse centromere specific minor satellite DNA probe; and (ii) immunolabelling of kinetochore proteins with CREST autoimmune serum. VP-16 caused significant increases in the frequencies of MN at all meiotic stages studied. VP-16 induced MN showed significantly el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 41 publications
3
30
0
Order By: Relevance
“…It has been reported that exposure of germ cells to ET results in a preferential localization of the aberrations near the centromere (20,23,24). We have observed a similar phenomenon in both MI and MII spermatocytes.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It has been reported that exposure of germ cells to ET results in a preferential localization of the aberrations near the centromere (20,23,24). We have observed a similar phenomenon in both MI and MII spermatocytes.…”
Section: Discussionsupporting
confidence: 84%
“…ET induced both aneuploidy and chromosomal structural aberrations in female germ cells (20,21) and, unlike any other chemical shown to induce aneuploidy in female germ cells (22), ET did so without causing a delay in meiotic progression (20). In male germ cells, ET induced fragmentation of centromeric DNA and micronuclei after exposure of primary spermatocytes (23,24). Diplotene-diakinesis I cells were the most sensitive to the action of ET (25).…”
mentioning
confidence: 99%
“…One is that these inhibitors 14 are not accessible to the tightly packed sperm nucleus. Another is that mature spermatozoa lack etoposide and merbarone targets.…”
Section: Discussionmentioning
confidence: 99%
“…Etoposide, a specific topoisomerase II inhibitor, caused both structural chromosome aberrations and aneuploidy in primary oocytes of the mouse [3,4] and the Chinese hamster [5]. Similar chromosomal effects of the inhibitor were found in mouse primary spermatocytes [6,7]. Another topoisomerase II inhibitor, merbarone, caused aneuploidy in mouse primary spermatocytes without formation of structural chromosome aberrations [8].…”
Section: Introductionmentioning
confidence: 69%